Talent identification and development: An academic review - Abbott, A.; Collins, D.; Martindale, R.; Sowerby, K. (Sport Scotland, 2002)
The Academic Review was commissioned to help evaluate Sportscotland's pilot Talent Identification and Development Programme which operated from early 2000 to the end of 2001. The Review highlights that the actual resources required for talent identification in the UK are concentrated on anthropometrical measures whereas the required resources should concentrate primarily on the psychological dimensions supported by the development of fundamental motor skills.